Optimizing the synthesis of poly(2,2'-bithiophene)-based semiconducting nanoparticles - Zhang, Yunchu (2015)
Semiconducting polymer-based nanoparticles (Pdots) have recently presented a promising prospect in fluorescence-labelling and biological sensing fields thanks to good photostabiligy, high photoluminescence (PL), low cytotoxicity compared to conventional dyes and semiconducting quantum dots (QDs) composed of heavy metals. In this thesis, 2,2'-bithiophene (BTh) was used as monomers to synthesize Pdots. The product was characterized by Fourier transform infrared spectroscopy (FTIR) for internal structure study and X-ray diffraction (XRD) for crystallinity. Excitation, emission as well as cell imaging were also investigated. Meanwhile in order to optimize the synthesis, Pdots were prepared under a series of varied time and voltage parameters, and their excitation range and maximum emission wavelength as well as intensity were analyzed and compared. It's proven that the electrochemical synthesis process is time and voltage dependent. The merits of Pdots mentioned above was also displayed during characterization. Moreover, other applications of Pdots, i.e. bioimaging and micro molecules tagging, are performed.